A novel g-C3N4 modified biosynthetic Fe(III)-hydroxysulfate for efficient photoreduction of Cr(VI) in wastewater treatment under visible light irradiation - Wang, Xuqian; Xie, Yi; Chen, Xiaowei; Zhou, Xiao; Hu, Wanrong; Li, Panyu; Li, Yonghong; Zhang, Yongkui; Wang, Yabo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •A novel g-C3N4-modified bio-Fe(III)-hydroxysulfate composite was synthesized.•Efficient photoreduction of Cr(VI) by g-C3N4@bio-Fe(III)-hydroxysulfate.•Photogenerated Fe(II), e− and O2– were identified as reactive reducing species.•The possible mechanism of photocatalytic reduction of Cr(VI) was proposed. Rational design of catalyst and reduction process are significant for the treatment of Cr(VI)-containing wastewater. In this work, for the first time, g-C3N4-modified biosynthetic Fe(III)-hydroxysulfate (g-C3N4@bio-Fe(III)-hydroxysulfate) composites were developed to achieve efficient Cr(VI) reduction under visible irradiation with the assistance of citric acid. By simple addition of g-C3N4 to cultivation medium of Acidithiobacillus ferrooxidans (A. ferrooxidans), g-C3N4@bio-Fe(III)-hydroxysulfate composites were obtained with improved productivities and surface properties. Compared with pure g-C3N4 and bio-Fe(III)-hydroxysulfate, the prepared composite exhibited higher photocatalytic activity in catalyst/citric acid/light system. Under optimized conditions (catalyst = 0.5 g L−1, citric acid = 1.0 mM and temperature = 25 °C), 100% reduction of 20 mg L−1 Cr(VI) could be achieved in 20 min without pH adjustment (initial pH = 3.13). The enhanced photocatalytic activity of g-C3N4@bio-Fe(III)-hydroxysulfate in the presence of citric acid mainly results from abundant reducing species (Fe(II), e− and O2–), accelerated electron-hole separation efficiency and enhanced Fe(II)/Fe(III) cycle. The strategy developed in this study provides new insights into the modification of bio-synthesized Fe(III)-hydroxysulfate and design of reductive system for the treatment of toxic Cr(VI)-containing wastewater.